The Effect of Choice Theory-Based Play Therapy on Aggression and Executive Functions in Single-Parent Children with Depression Symptoms - Mosafar, Atefeh; Nasri, Maryam (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to investigate the effectiveness of choice theory-based play therapy in reducing aggression and improving executive functions in single-parent children exhibiting symptoms of depression.Methods and Materials: Using a single-case experimental design, this applied research was conducted among children aged 6 to 8 from single-parent households in Birjand. After applying inclusion and exclusion criteria, three children were purposefully selected. Intervention was delivered over ten weekly 90-minute sessions using Nadery's choice theory-based play therapy protocol with mothers actively participating as co-therapists. Pre-test, four post-tests, and three follow-up assessments were administered. The data were collected using the Parent-Report BRIEF (executive functions), Vahedi et al.'s Aggression Questionnaire, and the Children’s Depression Inventory (CDI), and analyzed using visual, graphical, and statistical techniques (effect size, stable change index).Findings: The results showed a substantial reduction in aggression levels, with average improvement percentages of 66% post-intervention and 67% at two-month follow-up. All participants moved from above to below the clinical cut-off for aggression. Executive function improvements averaged 24% across participants, with notable gains in behavioral regulation, emotional control, and planning. Effect sizes ranged from 0.43 to 1.97. The intervention demonstrated consistent within-case and between-case effectiveness across all measures.Conclusion: Choice theory-based play therapy significantly enhanced executive functioning and reduced aggressive behavior in single-parent children with depressive symptoms. Involving parents as co-therapists and targeting core psychological needs through structured play proved to be a promising therapeutic approach.